Wasted Opportunities: When Schools Fail. Repetition and Drop-out in Primary Schools. Education for All: Status and Trends - Fiske, Edward B.; United Nations Educational, Scientific, and Cultural Organization, Paris (France). Education for All Forum Secretariat ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This report addresses the problem of school wastage in developing countries, provides the latest data on trends in repetition and drop-out, and deals with three questions: (1) how extensive is school wastage? (2) what are its causes? and (3) what can be done to make schools more efficient? Wastage is defined as the missed opportunities for individuals, communities, entire nations, and regions of the world. Finding ways to minimize 'school wastage' must play a central role in any serious effort to reach the goal of Education for All (EFA). Four parts are included in this report: (1) "The Goal of Education for All"; (2) "The Problem of School Wastage"; (3) "The High Cost of Wastage"; and (4) "What Can Be Done about School Wastage?" Many graphics and tables are included along with a glossary of 36 terms and a 20-item select bibliography. (LB)
Availability: Education for All, Forum Secretariat, United Nations Educational, Scientific, and Cultural Organization, 7 Place de Fontenoy, 75352 Paris 07 SP France; Tel: +33 (0)1 45 68 08 90.
Microfiche.
anannya
Keywords: Access to Education; Developing Nations; Dropouts; Educational Opportunities; Elementary Education; Enrollment Trends; Foreign Countries; Grade Repetition; Program Costs; School Holding Power; Student Costs; Tables (Data); World Declaration on Education for All